Well-Being During Coronavirus Disease 2019: A PICU Practical Perspective. Issue 8 (August 2020) - Donnelly, Peter D.; Davidson, Mark; Dunlop, Neil; McGale, Marie; Milligan, Eileen; Worrall, Mark; Wylie, Joanne; Kidson, Christopher
Abstract : The importance of promoting well-being for healthcare professionals has never been as important as during the current coronavirus disease 2019 pandemic. It is recognized that the concept of well-being is a multifaceted phenomenon which is influenced by individual, team, and system characteristics. We outline an approach to practically initiating supportive strategies within the PICU using a well-being approach to improve baseline resilience alongside an acute rescue strategy utilizing a peer-support network. These strategies are practical interventions and we share them with the aim of encouraging the international PICU community to use these or other strategies to support their teams. We encourage shared learning and collaboration during these difficult times. Abstract : Supplemental Digital Content is available in the text.